The last grudge : a ghosts of the past novel - Seeck, Max, 1985- (Seeck, Max, 1985- Ghosts of the past, 2023)
"While her colleagues investigate the brutal murder of a prominent businessman, Jessica Niemi must battle demons from her past in this terrifying new novel from the New York Times bestselling author of The Witch Hunter. Powerful executive Eliel Zetterborg has been found murdered in his upscale Helsinki home. What at first seems like a straightforward case soon proves to be anything but when it becomes clear the murderer has other targets. The only clue the police have is a photo of Zetterborg with three men whose faces have all been scratched off. Detective Jessica Niemi has taken some time off from her work with the Helsinki police to track down the coven that nearly killed her, and her partner, Yusuf, is assigned to lead the investigation. But as Yusuf delves into the case, he realizes he needs Jessica's help. And as they dig deeper, they realize that the evil they've been hunting all along has returned and is lying in wait for the right moment to strike"--